A double antibody sandwich ELISA for rapid diagnosis of virus infection and to measure the humoral response against infectious bursal disease on clinical material - Cardoso, T. C.; Sousa, RLM; Alessi, A. C.; Montassier, H. J.; Pinto, A. A. (Carfax Publ Co, 1998)
A double antibody sandwich ELISA (DAS-ELISA) was developed and employed for simultaneous direct detection of infectious bursal disease virus (IBDV) from bursal samples and to measure the humoral response, using the same basic immunoreagents, the purified and non-purified antigen, capture antibody and chicken hyperimmune sera were prepared, and standardized for this purpose, the DAS-ELISA was applied to both 80 bursal suspensions and 224 corresponding serum samples from vaccinated and non-vaccinated commercial hocks, Bursae samples were collected at 2 weeks of age, and submitted to histological examination, virus isolation in specific pathogen-free chickens embryos, and the DAS-ELISA technique, Serum titres obtained in indirect ELISA and serum neutralization test were compared with those in DAS-ELISA, the agreement was 80% between DAS-ELISA, and the conventional techniques, with high sensitivity (87%) and specificity (90%).